An appraisal of the application of Fiqh al-Hanafi under Islamic Family Law (Federal Territories) Act 1984 - Mohd, Azizah (IIUM Press, 2019)
Malaysia is a Muslim country consisting of thirteen States and Federal Territories (Kuala Lumpur, Labuan and Putrajaya). In principal, the official madhhab that is practised in Malaysia is Shafi’i Madhhab and this becomes common to all Malaysians even though it is not officially registered in the identification card of a Malaysian. Accordingly, in many religious affairs and practices, the society is based upon the principles or fiqh al-Shafi’i. Nevertheless, views of other Sunni madhhab is freely practiced by all Malaysians. Furthermore, the codification on Islamic law in the State Enactments in all States in Malaysia is based upon four Sunni schools of law. It follows that the Islamic law in Malaysia is not purely based on the Shafi’i madhhab and in many occasions adopted the view of Hanafi school depending on the adaptability of the opinion to the society. This article deals with the application of fiqh al-Hanafi under the Islamic Family Law (Federal Territories) Act 1984. Analysis will extend to the practices in the Malaysian Syariah Court when dealing with cases involving Muslims and the most appropriate view of the madhhab that is to be adopted by the Syariah Court in order to solve a particular issue. The study employs the qualitative method of study where it only involves library research. It is believed that this research will be beneficial to all who seek knowledge and useful to all researchers, academicians, legal practitioners, students and scholars.